The unintended consequences of divestment - Davies, Shaun William; Van Wesep, Edward Dickersin (Journal of Financial Economics, 2018)
A divestment campaign aims to depress share prices to induce managers to change firm behavior. Assuming that managers make profit-maximizing decisions in the absence of a campaign, firms that accede to divestors’ demands raise short-run share prices but depress long-run profits. Managers who are more interested in short-run prices are therefore more motivated by divestment than managers who care about long-run profits. We show that, as most managerial compensation contracts reward long-run profitability and stock returns, divestment can be ineffective at best, and perhaps counterproductive, rewarding managers who attract divestment campaigns. In a quantification exercise, we show that the wealth of most executives running likely divestment targets in 2015 would be unaffected by even large movements in share prices. Of those affected, a substantial majority would benefit from divestment.